Must love flowers a novel - Macomber, Debbie (New York Ballantine Books, 2023)
"Joan Sample is not living the life she expected. Now a widow and an empty-nester, she has become by her own admission something of a recluse. But after another birthday spent alone, she is finally inclined to listen to her sister, who has been begging Joan to reengage with the world. With her support, Joan gathers the courage to take some long-awaited steps: hiring someone to tame her overgrown garden, joining a grief support group, and even renting out a room to a local college student. Before long Joan is starting to feel a little like herself again. Across town, Maggie Herbert works mornings as a barista, tending to impatient customers before rushing to afternoon nursing classes. She's been living with her alcoholic father, ducking his temperamental outbursts and struggling to pay the household bills. But her circumstances brighten when she finds a room for rent in Joan's home. In the unexpected warmth of her new situation, Maggie finds a glimmer of hope for a better life. But will Maggie's budding attraction to one of her favorite customers ruin the harmony she's only recently found with Joan? Meanwhile, what is Joan to make of the mysterious landscaper who's been revitalizing her garden-a man who seems to harbor a past loss of his own? As Maggie and Joan confront unfamiliar life choices, they find themselves leaning on each other in surprising ways--discovering in the process that "family" is often just another word for love in all its forms"--
111991
Keywords: Self-realization in women -- Fiction; Female friendship -- Fiction; Widows -- Fiction; Interpersonal relations -- Fiction; Self-actualization (Psychology) in women -- Fiction; Older women -- Fiction; Man-woman relationship -- Fiction; Friendship -- Fiction; Domestic fiction; Fiction; Novels; Romance fiction